2018
DOI: 10.1002/jcp.27694
|View full text |Cite
|
Sign up to set email alerts
|

Ecto‐5′‐nucleotidase (CD73) is a potential target of hepatocellular carcinoma

Abstract: High expression of ecto‐5′‐nucleotidase (CD73) has been reported in a number of epithelium origin malignancies. Here, we hypothesize that CD73 promotes hepatocellular carcinoma (HCC) growth and metastasis and that the effect is mediated by epithelial growth factor receptor (EGFR). HCC cells with different malignancies and Tissue microarrays of the tumor and peritumoral liver tissues from 30 independent patients were used to examine CD73 and EGFR expression. Then, MTT and Ki67 detection, together with cell adhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…CD73 was significantly increased in patients with HCC and cirrhosis, and increased CD73 expression was associated with reduced overall survival of HCC (Sasikala et al, 2011; Sciarra et al, 2019; Snider et al, 2014). Mechanistically, adenosine produced by CD73 binds to adenosine A2A receptor and induces Rap1‐mediated membrane localization of P110β to activate PI3K/AKT signaling, and upregulates the expression of epidermal growth factor receptor in HCC, thereby promoting HCC growth and metastasis (Ma et al, 2019; Shali et al, 2019). Moreover, CD73 sustains cancer stem cells traits by upregulating SOX9 expression and enhancing its protein stability, further promoting HCC development and progression (Ma et al, 2020).…”
Section: Adenosinergic Pathway In Hccmentioning
confidence: 99%
“…CD73 was significantly increased in patients with HCC and cirrhosis, and increased CD73 expression was associated with reduced overall survival of HCC (Sasikala et al, 2011; Sciarra et al, 2019; Snider et al, 2014). Mechanistically, adenosine produced by CD73 binds to adenosine A2A receptor and induces Rap1‐mediated membrane localization of P110β to activate PI3K/AKT signaling, and upregulates the expression of epidermal growth factor receptor in HCC, thereby promoting HCC growth and metastasis (Ma et al, 2019; Shali et al, 2019). Moreover, CD73 sustains cancer stem cells traits by upregulating SOX9 expression and enhancing its protein stability, further promoting HCC development and progression (Ma et al, 2020).…”
Section: Adenosinergic Pathway In Hccmentioning
confidence: 99%
“…In HepG2 cells, we have already observed a correlation between a decrease in the expression levels of CD73 upon Abcc6 silencing [ 17 ] or probenecid treatment [ 18 ]. CD73 is the main source of extracellular adenosine in all tissues and is a key regulator in some tumor processes such as invasion, migration, and metastasis [ 12 , 13 ]. In this study, we found that the inhibition of CD73 activity by AOPCP ( Figure 5 E) mimicked the effect of probenecid in the filipodia retraction; however, the addition of adenosine together with probenecid preserved the filipodia architecture, suggesting that ABCC6 could modulate the extracellular adenosine availability with a combined action on the rate of ATP efflux and, at same time, on the expression levels of the CD73 enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…The ecto-5 -nucleotidase CD73 is able to catalyze the conversion of extracellular AMP to adenosine and phosphate; it is the main source of extracellular adenosine in all tissues in which ATP is poorly present in extracellular fluids [10,11]. CD73 is considered a key regulator in some cancer processes such as drug resistance, tumor metastasis, and tumor angiogenesis [12,13], therefore is an excellent candidate for cancer therapy [14][15][16]. In previous studies, we have reported that knockdown of Abcc6 in hepatocarcinoma cancer cells (HepG2), or the inhibition of its activity lead to the downregulation of NT5E gene, which codifies for the CD73 protein [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Studies examining how CD73 loss impacts HCC development in rodent models have not been performed, with the exception of a limited analysis reporting that subcutaneous inoculation of MHCC97‐derived tumors showed decreased growth in CD73 −/− compared to WT mice . Use of global and tissue‐specific CD73 knockout models in combination with standard HCC induction models, such as chemical carcinogenesis, fatty liver disease, and alcohol‐induced liver disease, will help address this question in a rigorous manner in future studies.…”
Section: Discussionmentioning
confidence: 99%